Sub‐Nanometer Confined Ions and Solvent Molecules Intercalation Capacitance in Microslits of 2D Materials. Issue 49 (22nd October 2021) - Guo, Yaqing; Hong, Xufeng; Su, Yaqiong; Luo, Wen; Yu, Ruohan; Wu, Jinsong; Hensen, Emiel J. M.; Mai, Liqiang; Cao, Yuancheng
Abstract: The ion intercalation behavior in 2D materials is widely applied in energy storage, electrocatalysis, and desalination. However, the detailed effect of ions on the performance, combining the influence of interlayer force and the change of solvent shell, is far less well understood. Here the solvated alkali metal ions with different sizes are intercalated into the lattice of 2D materials with different spacings (Ti3 C2 T x, δ‐MnO2, and reduced graphene oxide) to construct the intercalation model related with sub‐nanometer confined ions and solvent molecules to further understand the intercalation capacitance. Based on electrochemical methods and density functional theory calculation, the ions lose the electrostatic shielding solvent shell or shorten the distance between the layers, resulting in a significant increase in capacitance. It is found that the intercalation capacitance arises from the diffusion of solvated ions and is controlled by quantum and electrochemical capacitance for desolvated ions. This effect of solvation structure on performance can be applied in a variety of electrochemical interface studies and provides a new research view for energy storage mechanisms. Abstract : Solvent/ions cointercalation and desolvation process, to construct the intercalation model related with sub‐nanometer confined ions and solvent molecules (H2 O) to further optimize the intercalation capacitance model. Combining with the density functional theory calculation, it is found that the intercalation capacitance arises from the diffusion of solvated ion and controlled by quantum and electrochemical capacitance for desolvated ion.